EGFR-directed tyrosine kinase inhibitors for non-small cell lung cancer - Fatin Nur Elyana Mohd Sidek,; Muhammad Kumayl Abdulwahab,; Rashidi Dzul Keflee,; Mohammed Abdullah Alshawsh,; Suzita Mohd Noor,; Zarif Mohamed Sofian,; Azhar Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Non-small cell lung cancer (NSCLC) accounts for approximately 85% of all lung cancer cases and remains a leading cause of cancer-related deaths globally. While conventional chemotherapy has provided modest benefits, its toxicity and limited efficacy have underscored the need for more precise treatments. The identification of epidermal growth factor receptor (EGFR) mutations has transformed the therapeutic landscape, with EGFR tyrosine kinase inhibitors (EGFR-TKIs) significantly improving progression-free and overall survival in EGFR-mutant NSCLC. However, resistance mechanisms, such as T790M and C797S mutations have led to the development of successive generations of EGFR-TKIs. Fourth-generation inhibitors and combination therapies targeting bypass pathways now offer renewed hope for overcoming resistance. Nonetheless, the high cost and limited accessibility of these targeted therapies remain critical barriers, particularly in low- and middle-income countries. This review highlights the evolution of EGFR-TKIs, key resistance challenges, and economic considerations, emphasizing the need for equitable access to advance NSCLC treatment globally.